2017
DOI: 10.22159/ajpcr.2017.v10i4.16845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Canna Indica L. Extract Against Caffeine-Nicotine Co-Administration-Induced Exaggeration in Type 2 Diabetic Rats

Abstract: Objective: This study was designed to evaluate the protective effect of Canna indica L. extract against caffeine-nicotine administration-induced type 2 diabetes exaggeration in rats.Methods: A study was conducted for three weeks in four rat groups (n=6); viz.  type 2 diabetic control group, a caffeine-nicotine diabetic control group (20mg/kg, 0.4mg/kg, ip twice daily),  and Canna indica L. extract and caffeine-nicotine treatment group and  standard drug treated caffeine-nicotine diabetic group (Glibencamide, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Typhasterol was also found to be present in black tea ( Camellia sinensis , Theaceae) which exhibited an antihyperglycemic effect in rats [10] by insulin-enhancing activity [2] and reduced most of the diabetes-associated abnormalities [12] including hyperglycemia-induced renal oxidative stress and inflammation in streptozotocin-induced diabetic rats [14] . Presence of these pharmacologically active phytochemicals in HAE, supported the previously reported antidiabetic potential exhibited by C. indica L. roots and rhizomes [15] , [16] .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Typhasterol was also found to be present in black tea ( Camellia sinensis , Theaceae) which exhibited an antihyperglycemic effect in rats [10] by insulin-enhancing activity [2] and reduced most of the diabetes-associated abnormalities [12] including hyperglycemia-induced renal oxidative stress and inflammation in streptozotocin-induced diabetic rats [14] . Presence of these pharmacologically active phytochemicals in HAE, supported the previously reported antidiabetic potential exhibited by C. indica L. roots and rhizomes [15] , [16] .…”
Section: Resultssupporting
confidence: 84%
“…A decoction of the root with fermented rice is used in the treatment of gonorrhea and amenorrhea [13] . In our previous research articles [15] , [16] we reported antidiabetic activity of hydroalcoholic extract in normal rats as well as rats co-addicted with caffeine and nicotine. Since few decades, it has been used in constructed wetland for removal of organic pollutants, nitrogen, phosphorous and heavy metals [18] , [6] .…”
Section: Introductionmentioning
confidence: 99%